Access to justice on EU level: The long road to implement the Aarhus Convention - BECHTEL, Sebastian D. (The Opole Studies in Administration and Law, 2021)
More than 15 years after the EU’s accession to the Aarhus Convention, EU legislation does not yet ensure that members of the public have access to justice as envisaged by the Convention. Specifically, the possibilities to judicially challenge contraventions of EU environmental law by EU institutions and bodies remain very limited. The result is a lack of accountability to EU law, which undermines the rule of law and the protection of the environment and human health. This article describes the EU’s long road to implement the Convention. It analyses the EU’s current legislative proposal to amend the Aarhus Regulation and explains why it would not, in this form, suffice to ensure compliance with the Convention, leaving the Council and European Parliament to ensure that international law is respected. More broadly, the lengthy process reflects wider issues of the EU legal framework, related to the institutional balance and the overconstitutionalisation of the EU’s standing regime.